Spirulina platensis polysaccharides attenuate lipid and carbohydrate metabolism disorder in high-sucrose and high-fat diet-fed rats in association with intestinal microbiota. (September 2021) - Li, Tian-Tian; Huang, Zi-Rui; Jia, Rui-Bo; Lv, Xu-Cong; Zhao, Chao; Liu, Bin
Graphical abstract: Highlight: Spirulina platensis polysaccharides (SPLP) had significant hypolipidemic and hypoglycemic effects in HFD-fed rats. SPLP intervention modulate the hepatic steatosis and mRNA expressions involved in lipid and carbohydrate metabolism. SPLP altered the relative abundance of cecal short-chain fatty acids. SPLP significantly modulated the intestinal microbiota dysbiosis. Abstract: This study aimed to evaluate the possibility that Spirulina platensis crude polysaccharides may ameliorate the lipid and carbohydrate metabolism disorder, including obesity, hyperlipidemia, hyperglycemia, hepatic steatosis, and gut dysbiosis. The results showed Spirulina platensis crude polysaccharides could improve body weight, serum/liver lipid and carbohydrate indexes, and liver antioxidant parameters in high-sucrose and high-fat diet (HFD)-fed rats, which were accompanied by regulated liver mRNA expressions involved in lipid and carbohydrate metabolism disorder. In addition, SPLP intervention significantly decreased cecal level of propionic acid in HFD-fed rats. Notably, the SPLP could alter the relative abundance of Firmicutes, Bacteroides, Proteobacteria, and Actinobacteria at phylum levels. Based on Spearman's rank correlation coefficient, serum/liver lipid and carbohydrate profiles were found significantly positively correlated with genera Romboutsia, Allobaculum, Blautia, Phascolarctobacterium, Bifidobacterium, Coprococcus, Turicibacter, Erysipelotrichaceae_unclassified, Olsenella, Escherichia/Shigella, Coprobacillus, Lachnospiracea incertae, and Lactobacillus, but strongly negatively correlated with genera Atopostipes, Flavonifractor, Porphyromonadaceae_unclassified, Barnesiella, Oscillibacter, Paraprevotella, Jeotgalicoccus, Corynebacterium, Alloprevotella and Bacteroides . It was concluded that oral administration of SPLP could remarkably ameliorate the lipid and carbohydrate metabolism disorder and significantly modulate the intestinal microbiota in HFD-fed rats.